Connections Between Sub‐Cloud Coherent Updrafts and the Life Cycle of Maritime Shallow Cumulus Clouds in Large Eddy Simulation - Jian‐Feng Gu; Robert S. Plant; Christopher E. Holloway (Journal of Advances in Modeling Earth Systems)
Abstract We develop a novel approach to detect cloud‐subcloud coupling during the cloud life cycle and analyze a large eddy simulation of marine shallow cumulus based on the Barbados oceanographic and meteorological experiment campaign. Our results demonstrate how the activity of sub‐cloud coherent updrafts (SCUs) affect the evolution of shallow cloud properties during their life cycles, from triggering to development, and through to dissipation. Most clouds (∼80%) are related to SCUs during their lifetime but not every SCU (∼20% for short‐lived ones) leads to cloud formation. The fastest growing SCUs in a relatively moist region are most likely to initiate clouds. The evolution of cloud base mass‐flux depends on cloud lifetime. Compared with short‐lived clouds, longer lived clouds have longer periods of development, even normalized by the full lifetime, and tend to increase their cloud base mass‐flux to a stronger maximum. This is consistent with the evolution of mass flux near the top of SCU, indicating that the development of clouds is closely related to the sub‐cloud activity. When the SCUs decay and detach from the lifting condensation level, the corresponding cloud base starts to rise, signifying the start of cloud dissipation, during which the cloud top lowers to approach the rising cloud base. Previous studies have described similar conceptual pieces of this relationship but here we provide a continuous framework to cover all the stages of cloud‐subcloud coupling. Our findings provide quantitative evidence to supplement the conceptual model of shallow cloud life cycle and is critical to improve the steady‐state assumption in parameterization.